Paper Meets Plastic: The Perceived Environmental Friendliness of Product Packaging - Sokolova, Tatiana; Krishna, Aradhna; Döring, Tim (Journal of Consumer Research, 2023)
Abstract Packaging waste makes up more than 10% of the landfilled waste in the United States. While consumers often want to make environmentally friendly product choices, we find that their perceptions of the environmental friendliness of product packaging may systematically deviate from its objective environmental friendliness. Eight studies (N = 4,103) document the perceived environmental friendliness (PEF) bias whereby consumers judge plastic packaging with additional paper to be more environmentally friendly than identical plastic packaging without the paper. The PEF bias is driven by consumers’ “paper = good, plastic = bad” beliefs and by proportional reasoning, wherein packaging with a greater paper-to-plastic proportion is judged as more environmentally friendly. We further show that the PEF bias impacts consumers’ willingness to pay and product choice. Importantly, this bias can be mitigated by a “minimal packaging sticker” intervention, which increases the environmental friendliness perceptions of plastic-only packaging, rendering plastic-packaged products to be preferable to their plastic-plus-paper-packaged counterparts. This research contributes to the packaging literature in marketing and to research on sustainability while offering practical implications for managers and public policy officials.